Polarization of Regional Revenue and Expenditure Budget and General Allocation Fund as well as Effect on Regional Expenditure in Regency/City of East Kalimantan Province - Wahyuni, Erni; Michael, Michael; Amalia, Siti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze polarization of regional revenue and expenditure budget and general allocation fund as well as effect on regional expenditure in Regency/City of East Kalimantan Province. This type of research is quantitative research. The data uses secondary data. The data used is obtained from Regional Government Organization related to the realization of the Regency/City regional revenue and expenditure budget of East Kalimantan Province in 2011 to 2021. The data is contained in the Supreme Audit Agency of East Kalimantan Province. Data collection techniques by observation, document collection, and library research. Data analysis in this study used autoregressive distributed lag (ARDL). The results show that the general allocation of funds in a long run has a positive and significant effect. Regional expenditure in long run has a positive and significant effect. Regional income, general allocation funds, and regional expenditure in the short run have a positive and insignificant effect. Regional revenue and expenditure budget in 2014 to 2017 has decreased so that it can be said to be ineffective, then in the following year there is an increase so that it can be said to be effective. There is a decrease in general allocation of funds in the period from 2014 to 2015 which is 10.58% so that it could be said to be ineffective, then in the following year there is an increase of 22.48%. The following year is the same, so it is said to be effective.